Assessment of the Prevalence, Severity, Risk Factors of Anemia Among 2-12 Years of Aged Children Attending a Hospital in Western Uttar Pradesh Region (Academia Journal of Medicine, 2020)
Background: This study was done to create awareness among people about the problems of Anemia and health care providers in further management. The aim of this study was to assess the prevalence, severity, risk factors of anemia among 2-12 years of aged children attending a hospital. Subjects and Methods: Blood and stool samples were collected from the patient. Among those children with hemoglobin
Keywords: Hemoglobin; Children; Prevalence; Severity